If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x(-7 + i))(x(-7 + -1i))(x + 2) = y ((-7 * x + i * x))(x(-7 + -1i))(x + 2) = y Reorder the terms: ((ix + -7x))(x(-7 + -1i))(x + 2) = y ((ix + -7x))(x(-7 + -1i))(x + 2) = y (ix + -7x)((-7 * x + -1i * x))(x + 2) = y Reorder the terms: (ix + -7x)((-1ix + -7x))(x + 2) = y (ix + -7x)((-1ix + -7x))(x + 2) = y Reorder the terms: (ix + -7x)(-1ix + -7x)(2 + x) = y Multiply (ix + -7x) * (-1ix + -7x) (ix(-1ix + -7x) + -7x * (-1ix + -7x))(2 + x) = y ((-1ix * ix + -7x * ix) + -7x * (-1ix + -7x))(2 + x) = y Reorder the terms: ((-7ix2 + -1i2x2) + -7x * (-1ix + -7x))(2 + x) = y ((-7ix2 + -1i2x2) + -7x * (-1ix + -7x))(2 + x) = y (-7ix2 + -1i2x2 + (-1ix * -7x + -7x * -7x))(2 + x) = y (-7ix2 + -1i2x2 + (7ix2 + 49x2))(2 + x) = y Reorder the terms: (-7ix2 + 7ix2 + -1i2x2 + 49x2)(2 + x) = y Combine like terms: -7ix2 + 7ix2 = 0 (0 + -1i2x2 + 49x2)(2 + x) = y (-1i2x2 + 49x2)(2 + x) = y Multiply (-1i2x2 + 49x2) * (2 + x) (-1i2x2 * (2 + x) + 49x2 * (2 + x)) = y ((2 * -1i2x2 + x * -1i2x2) + 49x2 * (2 + x)) = y ((-2i2x2 + -1i2x3) + 49x2 * (2 + x)) = y (-2i2x2 + -1i2x3 + (2 * 49x2 + x * 49x2)) = y (-2i2x2 + -1i2x3 + (98x2 + 49x3)) = y (-2i2x2 + -1i2x3 + 98x2 + 49x3) = y Solving -2i2x2 + -1i2x3 + 98x2 + 49x3 = y Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-98x2' to each side of the equation. -2i2x2 + -1i2x3 + 98x2 + -98x2 + 49x3 = -98x2 + y Combine like terms: 98x2 + -98x2 = 0 -2i2x2 + -1i2x3 + 0 + 49x3 = -98x2 + y -2i2x2 + -1i2x3 + 49x3 = -98x2 + y Add '-49x3' to each side of the equation. -2i2x2 + -1i2x3 + 49x3 + -49x3 = -98x2 + -49x3 + y Combine like terms: 49x3 + -49x3 = 0 -2i2x2 + -1i2x3 + 0 = -98x2 + -49x3 + y -2i2x2 + -1i2x3 = -98x2 + -49x3 + y Reorder the terms: -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = -98x2 + 98x2 + -49x3 + 49x3 + y + -1y Combine like terms: -98x2 + 98x2 = 0 -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = 0 + -49x3 + 49x3 + y + -1y -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = -49x3 + 49x3 + y + -1y Combine like terms: -49x3 + 49x3 = 0 -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = 0 + y + -1y -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = y + -1y Combine like terms: y + -1y = 0 -2i2x2 + -1i2x3 + 98x2 + 49x3 + -1y = 0 The solution to this equation could not be determined.
| n/9-4=4 | | 6xy+8xy= | | (4x+3)-(9x+5)=0 | | 4x^2+13x-16=2-8x | | (x(-7+i))(x(-7-i))(x+2)=0 | | 39.2=p*112 | | 6n+18=(-2n)+2 | | 8-37a-15a^2=0 | | 14=y+13 | | -5.4=1 | | 2-6d=14 | | .11-x=.29 | | -4p^2-6p+15=0 | | n=-1.8 | | 2(x-1)-3x=-2 | | 4=-8y+1 | | (5x+3y)(3m+6w)= | | 4(x-9)=x+3(x-12) | | 5m^2-3m+3=2 | | 5=-3+2u | | 2=-4(g-2) | | 4(x-9)=x | | 10(n+2)=2 | | 3(x+4)-4(x-5)=63 | | 9(x+5)=2x+4x-15 | | 2x-(3+2x)+6= | | -27-4x=7(x+4) | | 4x-3(-6+x)=21 | | a^2+4a=25 | | 7(p-8)= | | (-15)-(6)= | | 2(7a+2)=88 |